A highly photoactive, visible-light-driven graphene/2D mesoporous TiO2 photocatalyst1. Issue 7 (6th July 2015) - Cho, Kyeong Min; Kim, Kyoung Hwan; Choi, Hyung Ouk; Jung, Hee-Tae
<x xml:space="preserve">Abstract</x> In this paper, we have reported a new, visible-light-driven photocatalyst composed of 2D mesoporous TiO2 on reduced graphene oxide, which enables enhanced absorption of visible light, showing outstanding charge separation ability, and a large surface area.